Association between food insecurity and fall-related injury among adults aged ≥65 years in low- and middle-income countries: The role of mental health conditions. (September 2021) - Smith, Lee; Shin, Jae Il; López-Sánchez, Guillermo F.; Veronese, Nicola; Soysal, Pinar; Oh, Hans; Grabovac, Igor; Barnett, Yvonne; Jacob, Louis; Koyanagi, Ai
Highlights: Data on 14, 585 adults aged ≥65 years (54.9% females) were analyzed. Severe food insecurity was associated with higher odds for injurious falls. A large proportion of this association was explained by mental health complications. Abstract: Purpose: We investigated the association between food insecurity and fall-related injury among older adults from six low- and middle-income countries (LMICs), and the extent to which this association is mediated by mental health. Methods: Cross-sectional, community-based, nationally representative data from the WHO Study on global AGEing and adult health (SAGE) were analyzed. Past 12-month food insecurity was assessed with two questions on frequency of eating less and hunger due to lack of food. Fall-related injury referred to those that occurred in the past 12 months. Multivariable logistic regression analysis and mediation analysis were conducted to assess associations. Results: Data on 14, 585 adults aged ≥65 years [mean (SD) age 72.5 (11.5) years; 54.9% females] were analyzed. After adjustment for potential confounders, severe food insecurity (versus no food insecurity) was associated with 1.95 (95%CI = 1.11–3.41) times higher odds for fall-related injury. Moderate food insecurity was not significantly associated with fall-related injury (OR = 1.34; 95%CI = 0.81–2.25). The mediation analysis showed that 37.3%, 21.8%, 17.7%, and 14.0% of the association between severe food insecurity and fall-related injury was explained by anxiety, sleep problems, depression, and cognition, respectively. Conclusion: Severe food insecurity was associated with higher odds for injurious falls among older adults in LMICs, and a large proportion of this association may be explained by mental health complications. Interventions to improve mental health among those who are food insecure and a strong focus on societal and government efforts to reduce food insecurity may contribute to a decrease in injurious falls.